The Rhaeto-Romance Languages - Beninca, Paolo (Romance Linguistics, 1992)
The Rhaeto-Romance languages have been known as such to the linguistic community since the pioneering studies of Ascoli and Gartner over a century ago. There has never been a community of RR speakers based on a common history or polity and the various dialects are mutually unintelligible, but a unity, based on a number of common features, has been advanced. This book is the first general description of the Rhaeto-Romance languages to be written in Eng. It provides a critical examination of the phonology, morphology, lexicon, and syntax of the modern Rhaeto-Romance dialects within the broader perspective of Romance comparative linguistics.